Aircraft noise propagation - the simplest case - Makarewicz, R.; Gołębiewski, R. (Archives of Acoustics, 2002)
Geometrical spreading, air absorption, and refraction are the main wave phenomena that govern the propagation of aircraft noise. The results of this study make possible the calculate noise at ground level in terms of the sound exposure level, LAE. The model applies to an aircraft with a nondirectional radiation pattern (e.g., helicopter, one-engine propeller) while the atmosphere is at rest. The derived equations provide some insight into the nature of noise propagation, that can be useful for teaching purposes.